Isotopic Composition of Precipitation in a Southeastern Region of Brazil during the Action of the South Atlantic Convergence Zone - Santos, Cleber (2021)
The use of stable isotopes of hydrogen and oxygen is a tool widely used to trace water paths along the hydrological cycle, providing support for understanding climatic conditions in different spatial scales. One of the main synoptic scale events acting in southeastern Brazil is the South Atlantic Convergence Zone (SACZ), which causes a large amount of precipitation from southern Amazonia to southeastern Brazil during the southern summer. In order to determine the isotopic composition of precipitation during the action of SACZ in Sao Francisco Xavier in southeastern Brazil, information from the Weather Forecasting and Climate Studies Center of the National Institute for Space Research (CPTEC) was used regarding SACZ performance days, the retrograde trajectories of the HYSPLIT model, and images from the GOES-16 satellite, in addition to the non-parametric statistical tests by Spearman and Kruskal-Wallis. A high frequency of air mass trajectories from the Amazon to southeastern Brazil was observed when the SACZ was operating. During the SACZ events, the average isotopic composition of precipitation was more depleted, with a delta O-18 of -9.9 parts per thousand (+/- 2.1 parts per thousand), a delta H-2 of -69.3 parts per thousand (+/- 17.9 parts per thousand), and d-excess of 10.1 parts per thousand (+/- 4.0 parts per thousand). When disregarding the SACZ performance, the annual isotopic composition can present an enrichment of 1.0 parts per thousand for delta O-18 and 8.8 parts per thousand for the delta H-2. The long-term monitoring of trends in the isotopic composition of precipitation during the SACZ events can assist in indicating the evapotranspiration contribution of the Amazon rainforest to the water supply of southeastern Brazil.